Origins of the Extinct, Subfossil Galápagos Giant Tortoises (Chelonoidis niger) of the Post Office Lava Tube (Inferior) of Floreana Island: Voluntary or Accidental Occupancy? - Moll, Don; Brown, Lauren E.; Resetar, Alan (Tropical Natural History, 2020)
The origins of the remains of giant tortoises that have accumulated in vast quantities on the floors of caves in some locations where giant tortoises once lived have received only scant attention to date. The subfossil Galápagos Giant Tortoises (Chelonoidis niger) of Floreana Island’s Post Office lava tube (inferior) are the main focus of this paper with supporting data obtained from other tortoise populations and locations. These remains have historically been explained, if at all, as the result of accidental falls (e.g., via pitfall traps). With the accumulation of greater knowledge of tortoise ecology and paleoecology the likelihood of voluntary cave entry and exit, sometimes by large numbers of giant tortoises (e.g., the Aldabra Atoll Giant Tortoises), also seems plausible. If followed by occasional blockages of exits by geological phenomena such as roof collapse the tortoises could be trapped within as well. An inquiry into the available evidence for the occurrence of both phenomena is the subject of this paper.